Modelling of 132kV overhead transmission lines by using ATP/EMTP for back-flashover pattern recognition / Nur Zawani Saharuddin - Nur Zawani, Saharuddin (2011)
Lightning overvoltage is the major cause of transmission-line outage in Malaysia. The phenomenon is a dominant factor considered in designing substations and transmission-line insulation, so its investigation is important. This study is thus essential to ensuring consistent performance of transmission lines and electric power system. The work models a 132kV overhead transmission line by using ATP-EMTP software, for back-flashover pattern recognition. It examines back-flashover studies, as they are essential to evaluation of lightning performance (in reality, most of the lightning strikes terminate at shield-wire rather than the phase-conductor). The full transmission-line model here is divided into several parts: wires (shield wires and phase conductors), towers, cross-arms, insulator strings, tower-surge impedance and towerfooting resistance. The developed model is then simulated with four magnitudes of lightning-strike current, to investigate the back-flashover voltage pattern across the line insulation of the transmission tower. The dissertation discusses effects of tower-footing resistance towards the back-flashover voltage observed. It presents the work’s findings, and recommends possible future works.